Blood transfusion following intended vaginal birth after cesarean vs elective repeat cesarean section in women with a prior primary cesarean: A population‐based record linkage study. (10th December 2018) - Pont, Sarah; Austin, Kathryn; Ibiebele, Ibinabo; Torvaldsen, Siranda; Patterson, Jillian; Ford, Jane
Abstract: Introduction: There is a lack of evidence around the risk of transfusion following vaginal birth after cesarean (VBAC) compared with elective repeat cesarean section (ERCS); this is important for decision‐making about birth options. The aim of this study was to determine transfusion rates and risk of transfusion following intended VBAC and ERCS. Material and methods: Women with a primary cesarean who had a subsequent birth at term (≥37 weeks) in New South Wales between 2000 and 2012, were identified from the New South Wales Perinatal Data Collection. Blood transfusions were identified from linked hospital records. Women deemed ineligible for VBAC were excluded. Modified Poisson regression was used to determine transfusion risk associated with intended VBAC compared with ERCS. Intended mode of birth was classified as: (1) intended VBAC and vaginal birth, (2) intended VBAC and cesarean, (3) intended ERCS and (4) "intention uncertain". Results: A total of 90 439 women were eligible for VBAC. Rates of transfusion were: 1.4% for intended VBAC and vaginal birth (n = 17 849); 1.2% for intended VBAC and cesarean (n = 7648); 0.3% for intended ERCS (n = 60 471); and 1.1% for "intention uncertain" (n = 4471). After adjusting for maternal and pregnancy characteristics, risk of transfusion was almost four times higher for women classified as intended VBAC than intended ERCS (adjusted risk ratio = 3.73, 95% confidence interval 2.90‐4.78). Conclusions: Following a prior primary cesarean, there was a higher risk of transfusion associated with attempting VBAC compared with ERCS. Though the absolute risk is small, it is important for women considering VBAC to choose birthing facilities with ready access to blood products.